Primary inflammatory myofibroblastic tumour of the liver: a clinicopathological and genetic study including a subset with ETV6:NTRK3 fusion. Issue 6 (21st February 2023) - Han, Qianqian; Zhang, Zhang; He, Xin; Chen, Min; Pang, Xiaojun; Chen, Chen; Du, Tianhai; Zhang, Hongying
Abstract : Aims: Inflammatory myofibroblastic tumour (IMT) is an intermediate neoplasm and rarely occurs in the liver. The aim of this study was to analyse the clinicopathological and genetic features of the largest primary hepatic IMT. Methods and results: A total of 10 cases were identified (four males and six females aged 1–48 years, median = 35 years) from 2011 to 2021, which accounted for 2.5% of IMTs occurring in all organ systems. Histological findings revealed that myofibroblastic/fibroblastic cells with inflammatory infiltration and focal hypocellularity were observed in three children. Immunostaining showed ALK‐diffuse cytoplasmic positive in six cases (six of 10; 60%) and pan‐TRK nuclear positive in three cases (three of 10; 30%). Hypercellular pattern was detected in ALK‐positive IMTs and obvious collagenous/myxoid matrix was observed in the pan‐TRK‐positive subgroup. ALK rearrangement was demonstrated in three of five interpretable ALK‐positive IMTs by fluorescence in‐situ hybridisation (FISH), and one case failed due to poor sample quality. Next‐generation sequencing indicated an IMT with TFG::ALK and FCHSD2::ALK fusion and TP53 mutation. ETV6::NTRK3 fusion was confirmed by RT‐PCR, but FISH‐negative results were found in two of three cases with pan‐TRK‐positive IMTs. No genetic alteration was detected in one tumour. One patient died 1 year after biopsy, while nine patients survived without evidence of disease in the follow‐up surveillance (17–119 months). Conclusions: This article describes the first example of primary paediatric hepatic IMTs with ETV6::NTRK3 fusion. Besides the common ALK‐positive subgroup, the proportion of NTRK3 fusion is high. Recognising the association between clinicopathological and molecular alterations is critical to accurate diagnosis of hepatic IMTs. Abstract : We present the largest clinicopathological analysis and molecular‐based investigation of primary liver IMT for consecutive 10‐year case series in an Asian population. Most of the liver IMTs were ALK‐positive and the rest were ETV6::NTRK3 fusion. This article describes the first example of primary paediatric hepatic IMT with ETV6::NTRK3 fusion.